PENGARUH KEPUASAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. DAYA ANUGRAH MANDIRI (DAYA MOTOR) CABANG BATURAJA - Rani Anwar; Leni Ariyani; Achmad Tarmizi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2023)
The study examined the influence of job satisfaction and work environment on employees’ performance at PT. Daya Anugrah Mandiri (Daya Motor) Baturaja Branch. The population for this study consisted of 32 respondents. The quantitative method was used, employing multiple linear regression analysis as the analytical tool. The analysis results indicated that the t-values for each variable, Job Satisfaction (X1) and Work Environment (X2), were 6.579 and 2.606, respectively. These values were greater than the critical t-value of 2.045, indicating that all variables had a significant influence on employees’ performance at PT. Daya Anugrah Mandiri (Daya Motor) Baturaja Branch. The calculated F-value of 124.612 was greater than the critical F-value of 3.33, suggesting that Job Satisfaction and Work Environment jointly had a significant influence on employees’ performance at PT. Daya Anugrah Mandiri (Daya Motor) Baturaja Branch. The coefficient of determination (R-squared) was 0.896, indicating that 89.6% of the employees’ performance (Y) could be explained by the variables Job Satisfaction (X1) and Work Environment (X2), while the remaining 10.4% was influenced by other variables not examined in this study. Based on the obtained analysis results, it was concluded that neglecting job satisfaction and work environment would enhance employees’ performance at PT. Daya Anugrah Mandiri (Daya Motor) Baturaja Branch.